Determination of Emotional Quotient (EQ) in Pencak Silat Athletes - Kencana, Manggar Mega Tri; Wiga Nurlatifa Romadhoni (UNIB Press, 2024)
This research aims to analyze the level of Emotional Quotient (EQ) of pencak silat athletes in Center for Education and Student Sports Training (PPLP) Central Java. Emotional quotient (EQ) is an important psychological factor that influences athletes' performance in facing competitive pressure. The EQ components measured include emotional stability, emotional strength, and emotional satisfaction. This research used a quantitative approach with a survey method, involving 14 athletes in the competition category. Data collection was carried out through the EQ test which consisted of 75 questions. The test results showed that in the EQ stability component, 42.9% of athletes were classified as very established, 50% were established, and 7.1% were less established. For EQ strength, 92.9% of athletes were in the balanced category and 7.1% were in the weak category. In the EQ satisfaction component, 42.9% of athletes felt very satisfied, 50% were satisfied, and 7.1% were disappointed. These results show that the majority of athletes have quite good emotional stability, but some still need improvement, especially in emotional satisfaction. Coaches are advised to pay more attention to developing the emotional aspects of athletes to support optimal performance in competition.